Computational simulation of nonlinear inelastic behavior of circular concrete-filled stainless-steel tubular short columns incorporating confinement effects. (1st January 2023) - Ahmed, Mizan; Gohari, Soheil; Sennah, Khaled; Chen, Wensu; Liang, Qing Quan
Highlights: A new confinement model is proposed for modeling concrete in CCFSST columns. A fiber-based computational simulation model of CCFSST short columns is developed. The fiber model includes confinement model and strain-hardening of stainless steel. The accuracy of various confinement models is assessed against experimental data. The modeling and design methods accurately predict structural performance. Abstract: This paper is concerned with the computational simulation, nonlinear inelastic behavior, and structural design of circular concrete-filled stainless-steel tubular (CCFSST) short columns subjected to axial compression accounting for confinement effects. A new confinement model is proposed for confined concrete based on extensive experimental data on CCFSST columns and implemented in the computational simulation model developed for CCFSST columns. A full-range three-stage stress–strain relationship for stainless steel is incorporated in the computational model that discretizes the column cross-section into fiber elements. The accuracy of the computational model of CCFSST columns is examined by comparison of computer solutions with experimental results of 125 CCFSST short columns documented elsewhere. A comparative study of various confinement models for predicting the axial capacities of CCFSST columns is presented. The computer model is employed to investigate the nonlinear inelastic behavior of CCFSST columns loaded concentrically to failure. The applicability of existing design codes for predicting the ultimate axial capacities of CCFSST columns is evaluated. A simple formula is proposed to calculate the ultimate strength of CCFSST short columns. It is demonstrated that the developed computer model simulates well the nonlinear inelastic behavior of CCFSST columns, and the proposed confinement model yields more accurate strength predictions than existing ones. Moreover, the proposed design method provides a better estimation of the strengths of CCFSST columns than current design codes.